2017
DOI: 10.1039/c6ay02647h
|View full text |Cite
|
Sign up to set email alerts
|

The human dimension: how social and behavioural research methods can help address microplastics in the environment

Abstract: The present paper illustrates the breadth of research methods in the Social and Behavioural Sciences and how these may be applied to the issue of environmental microplastics. Microplastics are a human-caused problem and we need to understand the human dimension in order to address it. Nine key points are emphasised in this paper and follow from the key observation that humans, through their perceptions, decisions and actions, are pivotal to the issue of primary and secondary microplastics in the environment: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…Informing people (raising awareness) is a necessary step, but studies have revealed assessing awareness alone does not necessarily assess if a change in attitude and behavior has been adopted (Schultz, 1999;Steg et al, 2013). Pahl and Wyles (2017) conclude that understanding the influences of human thought and behavior is just as important. Incorporating existing systematic understanding of human behaviors and their underlying mechanisms, with empirical methods to collect data that explain perceptions and behavior, thereby, enables a greater level of assessment of interventions aimed at behavior change (Reddy et al, 2016;Pahl and Wyles, 2017).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Informing people (raising awareness) is a necessary step, but studies have revealed assessing awareness alone does not necessarily assess if a change in attitude and behavior has been adopted (Schultz, 1999;Steg et al, 2013). Pahl and Wyles (2017) conclude that understanding the influences of human thought and behavior is just as important. Incorporating existing systematic understanding of human behaviors and their underlying mechanisms, with empirical methods to collect data that explain perceptions and behavior, thereby, enables a greater level of assessment of interventions aimed at behavior change (Reddy et al, 2016;Pahl and Wyles, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Pahl and Wyles (2017) conclude that understanding the influences of human thought and behavior is just as important. Incorporating existing systematic understanding of human behaviors and their underlying mechanisms, with empirical methods to collect data that explain perceptions and behavior, thereby, enables a greater level of assessment of interventions aimed at behavior change (Reddy et al, 2016;Pahl and Wyles, 2017).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Social and behavioural sciences have a lot to offer in addressing 'wicked' problems [23], where the issue is complex and ubiquitous, with complicated risk-benefit trade-offs that affect diverse stakeholders and seemingly threaten engrained habits and lifestyles. The behavioural disciplines need to develop and embrace this demand.…”
Section: Build Behavioural Science Capacitymentioning
confidence: 99%